2018
DOI: 10.5513/jcea01/19.1.2040
|View full text |Cite
|
Sign up to set email alerts
|

Development tendencies in crop production in Slovakia after 2004 – regional differentiations

Abstract: One of the key milestones of joining European Union was to decrease disparities within economical and social environment in Slovakia. On the contrary, disparities are still growing, also in agriculture. Structural changes in agriculture between 2004 and 2014 are explained based on several stages of development, leading to regional differentiations. Based on indicators of crop production such as -gross crop production, crop production (cereals, oil plants, potatoes, sugar beet and perennial fodder crops), produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Rudnicki (2009) hints at the deepening regional disparities in Polish agriculture. In the Czech Republic a similar topic was dealt with in the works of Kabrda and Jančák (2007) and by Slovakia Spišiak et al (2005), Kramáreková (2014, 2017), Némethová and Civáň (2017) and Némethová, Midler and Civáň (2018).…”
Section: Introductionmentioning
confidence: 75%
“…Rudnicki (2009) hints at the deepening regional disparities in Polish agriculture. In the Czech Republic a similar topic was dealt with in the works of Kabrda and Jančák (2007) and by Slovakia Spišiak et al (2005), Kramáreková (2014, 2017), Némethová and Civáň (2017) and Némethová, Midler and Civáň (2018).…”
Section: Introductionmentioning
confidence: 75%
“…In temperate and higher latitudes, as well as at elevated altitudes, an augmentation in agricultural productivity may be observed contingent upon the cultivated crop varieties, vegetative periods, precipitation levels, and temperature fluctuations [32,33]. For instance, in the context of mountainous regions of the Himalayas, it has been reported that the elevation in average temperatures due to climatic shifts has the potential to expedite the development and growth of winter crops, consequently enhancing crop yield [32].…”
Section: Introductionmentioning
confidence: 99%
“…Since 2009, crop production has dominated over livestock production in Slovakia. The share of crop production in the total gross agricultural output is currently 60% [9]. According to Věžník et al [10], Svobodová [11], Szabo et al [4] and Scriecia [12], similar trends of development in agricultural production are also occurring in other new member states (e.g., Czechia, Hungary, Romania) following EU accession.…”
Section: Introductionmentioning
confidence: 99%